Driving Character Excellence in the Digital Era: A SITOREM-Based Strategic Management of Local Wisdom and New Media in Vocational Education - Budiono, Kabul; Hardhienata, Soewarto; Suhendra, Suhendra (JURNAL AL-TANZIM, 2026)
This study aims to develop and evaluate an integrative character education model based on the local wisdom of wayang supported by new media in Vocational High Schools. This study uses a mixed-methods approach, combining quantitative analysis with Structural Equation Modeling–Partial Least Squares (SEM-PLS) and strategic optimization using SITOREM. The study population consisted of 258 teachers at a State Vocational High School in one district in Indonesia. The results show that the suitability of wayang story material, wayang-based character values, teacher motivation, the internalization of character values, and the interactivity of new media strongly influence the effectiveness of character education. SEM-PLS analysis confirmed that the proposed model met the goodness-of-fit criteria, indicating that the model is valid and reliable. Mediation analysis showed that character internalization and media interactivity did not significantly strengthen the effect of the main variables, indicating the need for additional reinforcing factors. The results of the SITOREM analysis identified priority areas for improvement, including honesty, exemplary behavior, spirituality, teacher motivation, student engagement, and media responsiveness. The implications of this research contribute to educational management by offering a culture- and data-based model to improve the effectiveness of character education through the integration of local wisdom, teacher roles, instructional design, and digital media.